Doppler spectra of medium grazing angle sea clutter; part 2: model assessment and simulation. Issue 1 (1st January 2016) - Watts, Simon; Rosenberg, Luke; Bocquet, Stephen; Ritchie, Matthew
Abstract : This study is concerned with the assessment of models of Doppler spectra, derived from high range resolution X‐band radar sea clutter observed from an airborne platform over the range of grazing angles, 15–45°. When looking up or downwind these models represent the strong correlation between mean Doppler shift and local spectrum intensity. When combined with random fluctuations of spectrum width, these characteristics give the spectra a temporal and spatial variability. The models are used to predict clutter spectrum statistics as a function of Doppler frequency and these are compared with statistics derived from the original data. It is also shown how realistic range‐varying coherent clutter returns can be simulated using the models.